Polymorphisms in the CIITA −168A/G (rs3087456) and CIITA +1614G/C (rs4774) may influence severity in multiple sclerosis patients - Pereira, Valéria Coelho Santa Rita; Fontes-Dantas, Fabrícia Lima; Paradela, Eduardo Ribeiro; Malfetano, Fabíola Rachid; Scherpenhuijzen, Simone de Souza Batista; Mansur, Letícia Fêzer; Luiz, Ronir Raggio; Oliveira, André Peres De; Farinhas, João Gabriel Dib; Maiolino, Ângelo; Alves-Leon, Soniza Vieira (Arquivos de Neuro-Psiquiatria, 2019)
It is currently unknown how genetic factors may influence the clinical course of multiple sclerosis (MS).Objective: We examined the impact of CIITA polymorphisms −168A/G (rs3087456) and +1614G/C (rs4774) on the risk of disability progression, severity and on responses to first-line immunomodulator treatments.Methods: Genomic DNA was extracted from blood samples. We used ABI3730xl and GeneMapper v.4.0 software to identify genotype variations. All patients were followed up and clinically reassessed at three-month intervals. Disability progression was measured by the Expanded Disability Status Scale and disease severity by the Multiple Sclerosis Spasticity Scale (MSSS).Results: We included 37 men and 80 women. We found no evidence regarding the influence of the single nucleotide polymorphisms studied in the Expanded Disability Status Scale or therapeutic response of the evaluated drugs. We performed a logistic regression analysis with the MSSS and found that a less severe MS course was associated with wild type CIITA −168AA and CIITA +1614GG, as the chance of the patient progressing to MSSS2 and MSSS3 decreased in 61% and 75% with CIITA −168AA and 66% and 75% with CIITA +1614GG, respectively (p < 0.0001). Although less significant, the CIITA +1614 GC also pointed to a less severe MS course and the chance of the patient progressing to MSSS3 decreased 79% (p = 0.015). We also observed that the CIITA −168GG genotype was more frequent in MSSS2 and MSSS3 and had 40% lower odds ratio to becoming more severe MS.Conclusion: These data suggest that CIITA −168AA, CIITA +1614GG and CIITA +1614 GC polymorphisms may be associated with a better MS clinical course. This knowledge may be useful for a better understanding of MS and its therapeutic management.
Keywords: Multiple sclerosis; Polymorphism, Genetic; Therapeutics; Disease progression